A simplified curcumin targets the membrane of Bacillus subtilis - Morao, Luana G. [UNESP] (2019)
Curcumin is the main constituent of turmeric, a seasoning popularized around the world with Indian cuisine. Among the benefits attributed to curcumin are anti-inflammatory, antimicrobial, antitumoral, and chemopreventive effects. Besides, curcumin inhibits the growth of the gram-positive bacterium Bacillus subtilis. The anti-B. subtilis action happens by interference with the division protein FtsZ, an ancestral tubulin widespread in Bacteria. FtsZ forms protofilaments in a GTP-dependent manner, with the concomitant recruitment of essential factors to operate cell division. By stimulating the GTPase activity of FtsZ, curcumin destabilizes its function. Recently, curcumin was shown to promote membrane permeabilization in B. subtilis. Here, we used molecular simplification to dissect the functionalities of curcumin. A simplified form, in which a monocarbonyl group substituted the beta-diketone moiety, showed antibacterial action against gram-positive and gram-negative bacteria of clinical interest. The simplified curcumin also disrupted the divisional septum of B. subtilis; however, subsequent biochemical analysis did not support a direct action on FtsZ. Our results suggest that the simplified curcumin exerted its function mainly through membrane permeabilization, with disruption of the membrane potential necessary for FtsZ intra-cellular localization. Finally, we show here experimental evidence for the requirement of the beta-diketone group of curcumin for its interaction with FtsZ.